Psychometric properties of a driving self-efficacy scale – short form in Argentinean drivers - Trogolo, Mario Alberto (2017)
The purpose of this study was to translate and examine the psychometric properties of a driving self-efficacy scale developed by Dorn and Machin (2004). The factor structure, reliability and external validity of the scale were examined in a sample of 447 drivers from Cordoba, Argentina. In addition, measurement invariance across sex was also tested. Results from a confirmatory factor analysis support the unidimensional structure of the scale and the invariance of its parameters (configural, metric and scalar) between men and women. Reliability analyses using alpha and omega coefficients revealed high internal consistency (coefficients equal to 0.81 in both cases) and satisfactory evidence of external validity of the scale scores, with measures of risk perception, risky driving, history of traffic crashes and fines. Finally, results also showed that the scale seems to be relatively robust against response biases due to social desirability. In summary, findings support the validity and reliability of the scale in Argentina. However, further studies analyzing additional psychometric properties are needed.  DOI: https://doi.org/10.24265/liberabit.2017.v23n1.02